2019
DOI: 10.5539/ibr.v12n7p76
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Management and Operational Performance of Manufacturing Firms in South-East Nigeria

Abstract: This study aims to ascertain the relationship between inventory management and operational performance of quoted manufacturing firms in the south-east; one of the geographic regions with high industrialization prospects in Nigeria. To achieve this, operational performance of manufacturing firms and their association with components of inventory management; inventory cost, just-in-time approach, materials requirement planning and strategic supplier partnership, was examined through a questionnaire. Three hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The study found a significant effect of VMI on performance of mining supply chains. This is in tandem with other studies that have put SC strategies to scrutiny (Obura, 2015; John et al ., 2015; Atnafu and Balda, 2018; Mbah et al , 2019). A study by John et al (2015) found that there is significant impact between effective management of inventory and OP in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found a significant effect of VMI on performance of mining supply chains. This is in tandem with other studies that have put SC strategies to scrutiny (Obura, 2015; John et al ., 2015; Atnafu and Balda, 2018; Mbah et al , 2019). A study by John et al (2015) found that there is significant impact between effective management of inventory and OP in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is the need to quantify the role of leadership and digital resources in the implementation of VMI. According to the studies by Gitau (2016) and John et al (2015), inventory management affects operational and financial efficiency (Mbah et al , 2019). These aspects of the organization may not directly transmute into profitability but activates performance through VMI adoption.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Organizational Performance in Public Sectors Oballah, Waiganjo, and Wachiuri's (2015) study examines how inventory management practises affect businesses' performance in Kenya's public health industry. The study found that shrinkage of inventory has a negative influence on a firm's performance, whereas inventory accuracy has a positive impact on organisational success (Mbah et al, 2019). Pitts and Lie (2006) examined the effects of inactivity on the volume of inventory produced by information insecurity in a survey carried out at the US Navy base in Rhode Island, and can currently be considered pioneers in the research of accuracy (Pitts & Lie, 2006).…”
Section: The Impact Of Inventory Accuracy Of Inventory Management Onmentioning
confidence: 99%
“…Manufacturing industries continue to exhibit an imperative role in the growth of established (Peng, Zhang, & Chang, 2021;Signé, 2018) and developing economies (Mbah, Obiezekwem, & Okuoyibo, 2019;Opoku, Fiati, Kaku, Ankomah, & Opoku-Agyemang, 2020). Manufacturing has historically provided the government with employment possibilities, creative thinking, and financial resources through gross domestic product (GDP) and taxes (Akoto, Awunyo-Vitor, & Angmor, 2013;Bawa, Asamoah, & Kissi, 2018).…”
Section: Introductionmentioning
confidence: 99%